Process for the production of a filament geotextile with added tourmaline powder

CN120776517BActive Publication Date: 2026-10-27XINJIANG LUDE NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511069707.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2026-10-27
Estimated Expiration
2045-07-31

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种添加电气石粉体的长丝土工布制备方法,以解决电气石粉体在聚丙烯中分散不均匀的问题,制得具有良好力学性能的长丝土工布

Benefits of technology

本发明通过硅烷偶联剂和氧化石墨烯对电气石进行表面改性,显著提高了电气石与高分子基体的界面结合力,同时高分子基体合金化处理是将聚丙烯进行合金化处理,形成合金化高分子基体,改变了聚丙烯的性能,从而有利于电气石粉体更好地与合金化高分子基体混合,进一步提高了土工布的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120776517B_ABST
    Figure CN120776517B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of filament geotextile preparation methods, and particularly relates to a filament geotextile preparation method with added tourmaline powder, which comprises the following steps: raw material pretreatment: tourmaline powder surface modification treatment is performed on the tourmaline powder, and high polymer matrix alloying treatment is performed on the high polymer matrix; composite master batch preparation: the surface modified tourmaline powder is melt blended with the alloyed high polymer matrix to prepare a composite master batch; gradient spinning forming: a three-zone temperature control spinning process is adopted in combination with a special-shaped spinneret hole setting to prepare functional filaments; dynamic magnetic field drafting: a directional magnetic field is applied in a hot roller drafting process to induce ordered arrangement of tourmaline particles; nanofiber synergistic laying: electrospun nanofibers are synchronously introduced to form a micron-nanometer composite fiber net; pulse needling consolidation; and functional activation post-treatment. The application is favorable for better mixing of the tourmaline powder and the alloyed high polymer matrix, and further improves the performance of the geotextile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of long-filament geotextile preparation methods, specifically a method for preparing long-filament geotextile with added tourmaline powder. Background Technology

[0002] Tourmaline is a natural mineral, primarily composed of silicates, possessing spontaneous polarity and capable of generating piezoelectric and thermoelectric effects. This property makes tourmaline widely used in many fields, such as electronic equipment, medical devices, and environmental protection equipment. Geotextiles are commonly used as building materials in civil engineering, primarily for soil reinforcement, preventing soil erosion, and controlling groundwater levels.

[0003] In the preparation of existing geotextiles with added tourmaline powder, uneven dispersion of tourmaline in polypropylene can cause breakage of the extruded filaments, thus affecting the performance of the geotextile. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing filament geotextile with added tourmaline powder, so as to solve the problem of uneven dispersion of tourmaline powder in polypropylene and obtain filament geotextile with good mechanical properties.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is: to provide a method for preparing a long-filament geotextile with added tourmaline powder, comprising the following steps: Raw material pretreatment: The tourmaline powder is subjected to surface modification treatment, and the polymer matrix is ​​subjected to polymer matrix alloying treatment; Composite masterbatch preparation: Surface-modified tourmaline powder is melt-blended with an alloyed polymer matrix to prepare composite masterbatch; Gradient spinning: A three-zone temperature-controlled spinning process, combined with irregularly shaped spinnerets, is used to prepare functional filaments; Dynamic magnetic field drawing: A directional magnetic field is applied during the hot roller drawing process to induce the tourmaline particles to arrange in an orderly manner; Synergistic nanofiber web formation: Electrospun nanofibers are introduced simultaneously to form a micron-nano composite fiber web; Pulse needle bonding: Servo-driven pulse needle bonding process is used to enhance the bonding force between fibers and retain functional activity; Post-functionalization treatment: Low-temperature plasma treatment is used to enhance the surface energy of the material and the exposure of functional groups.

[0006] Optionally, the raw material pretreatment includes the following steps: The surface modification treatment of tourmaline powder adopts a two-step method: first, pretreatment with a silane coupling agent solution with a mass fraction of 2-5% is performed, and then coating with graphene oxide nanosheets accounting for 1-3% of the mass of tourmaline to obtain modified tourmaline powder. The polymer matrix alloying process involves blending polypropylene and ethylene-octene copolymer at a mass ratio of 90:10-80:20, adding antioxidants and light stabilizers, and then melt-blending the mixture using a twin-screw extruder to obtain the alloyed polymer matrix.

[0007] Optionally, the preparation of the composite masterbatch includes the following steps: Surface-modified tourmaline powder is mixed with alloyed polymer matrix at a mass ratio of 20:80-40:60, and dispersant and lubricant are added. Melt blending is carried out using a two-stage twin-screw extruder, with a first-stage extrusion temperature of 220-240℃, a second-stage extrusion temperature of 240-260℃, and a screw speed of 300-400 rpm. After water cooling and pelletizing, the extrudate is used to obtain a composite masterbatch with uniform tourmaline content.

[0008] Optionally, the gradient spinning process includes the following steps: The composite masterbatch is conveyed to the spinning box via a screw extruder. The spinning box is divided into three temperature zones: The temperature in the feeding zone is 260-270℃; The temperature in the metering zone is 255-265℃; The temperature in the spinneret area is 250-260℃; The spinneret has irregularly shaped holes with an orifice diameter of 0.15-0.25 mm.

[0009] Optionally, the dynamic magnetic field stretching includes the following steps: The nascent fibers are drawn through three stages of hot rollers: the temperature of the first hot roller is 60-80℃, the temperature of the second hot roller is 100-120℃, and the temperature of the third hot roller is 80-95℃. An axial magnetic field with a strength of 0.05-0.15T is applied in the second hot roller region. The direction of the magnetic field is consistent with the fiber drawing direction, which causes the tourmaline particles to align axially along the fiber. The total draw ratio is 3.5-5.0 times, and the draw speed is 800-1500 m / min.

[0010] Optionally, the synergistic nanofiber web formation includes the following steps: Core-shell nanofibers were prepared using coaxial electrospinning technology, with polylactic acid as the core and polyurethane loaded with nano-titanium dioxide as the shell. The electrospinning parameters were set as follows: voltage 18-25kV, receiving distance 12-18cm, and feed rate 0.5-1.5mL / h. During the filament web laying process, nanofibers are simultaneously and evenly sprayed onto the filament web, with the mass of nanofibers accounting for 1-5% of the mass of the filament web.

[0011] Optionally, the pulsed needle consolidation includes the following steps: A servo-driven pulse needle punching machine is used to consolidate the fiber web. The needle punching process consists of three stages: Pre-needling stage: The needling frequency is 600-800 times / min, the needling depth is 4-6mm, and the needling density is 5-10 needles / cm²; Main needling stage: Needling frequency is 800-1200 times / min, needling depth is 6-10mm, needling density is 20-40 needles / cm², and high-frequency pulses of 200-300 times / min are applied at the same time. Shaping stage: The acupuncture frequency is 400-600 times / min, the acupuncture depth is 2-4mm, and the acupuncture density is 5-10 needles / cm²; The acupuncture needles are of double or triple hook structure and are size 28-36.

[0012] Optionally, the post-activation processing of the function includes the following steps: The needle-punched and consolidated geotextile was subjected to low-temperature plasma treatment. The gas medium was a mixture of argon and oxygen with a volume ratio of 3:1-5:1. The processing parameters are: power density 50-100W / m², processing time 10-30s, and working air pressure 20-50Pa. After treatment, the geotextile is subjected to heat setting at a temperature of 120-140℃ for 30-60 seconds.

[0013] Compared with the prior art, the present invention has the following beneficial effects: This invention modifies the surface of tourmaline using silane coupling agents and graphene oxide, significantly improving the interfacial bonding force between tourmaline and the polymer matrix. Simultaneously, the polymer matrix alloying treatment involves alloying polypropylene to form an alloyed polymer matrix, which alters the properties of polypropylene. This facilitates better mixing of tourmaline powder with the alloyed polymer matrix, further improving the performance of the geotextile. Attached Figure Description

[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0015] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0016] Example 1 Raw material pretreatment Tourmaline powder modification: 10 kg of tourmaline powder with a particle size of 1 μm was added to 50 L of 3% silane coupling agent solution and stirred at 60 °C for 45 minutes. Then, 200 g of graphene oxide nanosheets were added and ultrasonically dispersed for 30 minutes to coat the tourmaline surface with graphene oxide nanosheets, thereby obtaining modified tourmaline powder. The modified tourmaline powder was then filtered through a 120-mesh filter and dried for later use, so that the moisture content of the modified tourmaline powder was less than 15%.

[0017] Polymer matrix alloying: 85 kg of polypropylene and 15 kg of ethylene-octene copolymer were blended, and 0.5 kg of antioxidant and 0.3 kg of light stabilizer were added. The mixture was then melt-blended using a twin-screw extruder to prepare an alloyed polymer matrix.

[0018] Preparation of composite masterbatch 30 kg of modified tourmaline powder was mixed with 70 kg of alloyed polymer matrix, and 2 kg of calcium stearate dispersant and 1 kg of polyethylene wax lubricant were added. The mixture was then processed using a two-stage twin-screw extruder to prepare composite masterbatch. The first-stage extrusion temperature was 230℃, the second-stage extrusion temperature was 250℃, and the screw speed was 350 rpm. After water cooling and pelletizing, the extrudate yielded composite masterbatch with a uniform tourmaline content.

[0019] Gradient spinning The composite masterbatch is conveyed to the spinning box via a screw extruder. The spinning box temperature is set as follows: 265℃ in the feeding zone, 260℃ in the metering zone, and 255℃ in the spinneret zone. The spinneret uses a trilobal orifice with a diameter of 0.2mm.

[0020] After the molten material is extruded through the spinneret, it is cooled and shaped under the action of side blowing air. The side blowing air temperature is 20℃ and the air speed is 0.5m / s.

[0021] Dynamic magnetic field stretching The nascent fibers are drawn through three stages of hot rollers: the first hot roller has a temperature of 70°C, the second hot roller has a temperature of 110°C, and the third hot roller has a temperature of 90°C.

[0022] An axial magnetic field of 0.1T is applied in the second hot roll region, the total draw ratio is 4.0, and the draw speed is 1200m / min.

[0023] Nanofiber synergistic web formation Nanofibers were prepared using coaxial electrospinning technology, with polylactic acid as the core layer and polyurethane loaded with nano-titanium dioxide as the shell layer. The electrospinning parameters were set as follows: voltage 20 kV, receiving distance 15 cm, and feed rate 1.0 mL / h.

[0024] During the filament web laying process, nanofibers are simultaneously sprayed onto the filament web, and the mass of the nanofibers accounts for 3% of the mass of the filament web.

[0025] Pulse acupuncture consolidation A servo-driven pulse needle punching machine is used to consolidate the fiber web. The pre-needling stage has a frequency of 700 pulses / min and a needle depth of 5 mm; the main needle punching stage has a base frequency of 1000 pulses / min, superimposed with a high-frequency pulse of 250 pulses / min, and a needle depth of 8 mm; the shaping stage has a frequency of 500 pulses / min and a needle depth of 3 mm. The needle density is 30 needles / cm², and the needle size is 32.

[0026] Post-activation processing The needle-punched and consolidated geotextile was subjected to low-temperature plasma treatment using a mixture of argon and oxygen in a volume ratio of 4:1. The treatment parameters were: power density 80 W / m², treatment time 20 s, and working pressure 30 Pa. After treatment, the geotextile is subjected to heat setting at 130℃ for 45 seconds.

[0027] Performance testing Mechanical properties: breaking strength is 48.5 kN / m, and breaking elongation is 38%.

[0028] Functional performance: 24-hour negative ion release is 1850 ions / cm³, and far-infrared emissivity is 92%.

[0029] Adsorption and degradation performance: The adsorption rate for methylene blue was 90%, and the photocatalytic degradation rate after 2 hours of UV irradiation was 78%.

[0030] Microstructure: Scanning electron microscopy revealed that the tourmaline particles were oriented in the fibers with an orientation degree of 82%; the nanofibers formed a uniform mesh coating layer on the surface of the micron-long filaments with a coverage rate of 45%.

[0031] Example 2 Raw material pretreatment Tourmaline powder modification: 10 kg of tourmaline powder with a particle size of 1 μm was added to 50 L of 5% silane coupling agent solution and stirred at 60 °C for 45 minutes. Then, 600 g of graphene oxide nanosheets were added and ultrasonically dispersed for 30 minutes to coat the tourmaline surface with graphene oxide nanosheets, thereby obtaining modified tourmaline powder. The modified tourmaline powder was then filtered through a 120-mesh filter and dried for later use, so that the moisture content of the modified tourmaline powder was less than 15%.

[0032] Polymer matrix alloying: 80 kg of polypropylene and 20 kg of ethylene-octene copolymer were blended, and 0.5 kg of antioxidant and 0.3 kg of light stabilizer were added. The mixture was then melt-blended using a twin-screw extruder to prepare an alloyed polymer matrix.

[0033] Preparation of composite masterbatch 40 kg of modified tourmaline powder was mixed with 60 kg of alloyed polymer matrix, and 2 kg of calcium stearate dispersant and 1 kg of polyethylene wax lubricant were added. The mixture was then processed using a two-stage twin-screw extruder to prepare composite masterbatch. The first-stage extrusion temperature was 230℃, the second-stage extrusion temperature was 250℃, and the screw speed was 400 rpm. After water cooling and pelletizing, the extrudate yielded composite masterbatch with a uniform tourmaline content.

[0034] Gradient spinning The composite masterbatch is conveyed to the spinning box via a screw extruder. The spinning box temperature is set as follows: 270℃ in the feeding zone, 265℃ in the metering zone, and 260℃ in the spinneret zone. The spinneret uses a trilobal orifice with a diameter of 0.2mm.

[0035] After the molten material is extruded through the spinneret, it is cooled and shaped under the action of side blowing air. The side blowing air temperature is 20℃ and the air speed is 0.5m / s.

[0036] Dynamic magnetic field stretching The nascent fibers are drawn through three stages of hot rollers: the first hot roller has a temperature of 70°C, the second hot roller has a temperature of 110°C, and the third hot roller has a temperature of 90°C.

[0037] An axial magnetic field of 0.15T is applied in the second hot roll area, the total draw ratio is 4.5 times, and the draw speed is 1200m / min.

[0038] Nanofiber synergistic web formation Nanofibers were prepared using coaxial electrospinning technology, with polylactic acid as the core layer and polyurethane loaded with nano-titanium dioxide as the shell layer. The electrospinning parameters were set as follows: voltage 25 kV, receiving distance 15 cm, and feed rate 1.0 mL / h.

[0039] During the filament web laying process, nanofibers are simultaneously sprayed onto the filament web, with the nanofibers accounting for 5% of the mass of the filament web.

[0040] Pulse acupuncture consolidation A servo-driven pulse needle punching machine is used to consolidate the fiber web. The pre-needling stage has a frequency of 700 pulses / min and a needle depth of 5 mm; the main needle punching stage has a base frequency of 1200 pulses / min, superimposed with a high-frequency pulse of 250 pulses / min, and a needle depth of 10 mm; the shaping stage has a frequency of 500 pulses / min and a needle depth of 3 mm. The needle density is 30 needles / cm², and the needle size is 32.

[0041] Post-activation processing The needle-punched and consolidated geotextile was subjected to low-temperature plasma treatment using a mixture of argon and oxygen in a volume ratio of 4:1. The treatment parameters were: power density 100 W / m², treatment time 30 s, and working pressure 30 Pa. After treatment, the geotextile is subjected to heat setting at 130℃ for 45 seconds.

[0042] Performance testing Mechanical properties: breaking strength is 52.3 kN / m, and breaking elongation is 35%.

[0043] Functional performance: 2100 negative ions / cm³ are released in 24 hours, and the far-infrared emissivity is 94%.

[0044] Adsorption and degradation performance: The adsorption rate for methylene blue was 92%, and the photocatalytic degradation rate after 2 hours of UV irradiation was 82%.

[0045] Comparative Example Long-filament geotextiles were prepared using traditional processes without tourmaline surface modification, magnetic field application, or addition of nanofibers.

[0046] Table 1 compares the performance of the filament geotextiles prepared in the examples and comparative examples.

[0047] As can be seen from the data in Table 1, the filament geotextile prepared by this invention is significantly superior to products prepared by traditional processes in terms of both mechanical properties and ecological functions. Through multi-scale structural control technology, uniform dispersion and directional arrangement of tourmaline in the polymer matrix, as well as synergistic reinforcement by micron-sized filaments and nanofibers, were achieved, thus giving the material both high strength and multifunctional properties.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a long-filament geotextile with added tourmaline powder, characterized in that, Includes the following steps: Raw material pretreatment: The tourmaline powder is subjected to surface modification treatment, and the polymer matrix is ​​subjected to polymer matrix alloying treatment; Composite masterbatch preparation: Surface-modified tourmaline powder is melt-blended with an alloyed polymer matrix to prepare composite masterbatch; Gradient spinning: A three-zone temperature-controlled spinning process, combined with a shaped spinneret design, is used to prepare functional filaments; Dynamic magnetic field drawing: A directional magnetic field is applied during the hot roller drawing process to induce the tourmaline particles to arrange in an orderly manner; Synergistic nanofiber web formation: Electrospun nanofibers are introduced simultaneously to form a micron-nano composite fiber web; Pulse needle bonding: Servo-driven pulse needle bonding process is used to enhance the bonding force between fibers and retain functional activity; Post-functional activation treatment: Low-temperature plasma treatment is used to enhance the surface energy of the material and the exposure of functional groups; The raw material pretreatment includes the following steps: The surface modification treatment of tourmaline powder adopts a two-step method: first, pretreatment with a silane coupling agent solution with a mass fraction of 2-5% is performed, and then coating with graphene oxide nanosheets accounting for 1-3% of the mass of tourmaline to obtain modified tourmaline powder. The polymer matrix alloying treatment is carried out by blending polypropylene and ethylene-octene copolymer at a mass ratio of 90:10-80:20, adding antioxidants and light stabilizers, and then melt-blending through a twin-screw extruder to prepare the alloyed polymer matrix. The dynamic magnetic field stretching includes the following steps: The nascent fibers are drawn through three stages of hot rollers: the temperature of the first hot roller is 60-80℃, the temperature of the second hot roller is 100-120℃, and the temperature of the third hot roller is 80-95℃. An axial magnetic field with a strength of 0.05-0.15T is applied in the second hot roller region. The direction of the magnetic field is consistent with the fiber drawing direction, which causes the tourmaline particles to align axially along the fiber. The total draw ratio is 3.5-5.0 times, and the draw speed is 800-1500 m / min; The pulsed needle acupuncture consolidation includes the following steps: A servo-driven pulse needle punching machine is used to consolidate the fiber web. The needle punching process consists of three stages: Pre-needling stage: The needling frequency is 600-800 times / min, the needling depth is 4-6mm, and the needling density is 5-10 needles / cm²; Main needling stage: Needling frequency is 800-1200 times / min, needling depth is 6-10mm, needling density is 20-40 needles / cm², and high-frequency pulses of 200-300 times / min are applied at the same time. Shaping stage: The acupuncture frequency is 400-600 times / min, the acupuncture depth is 2-4mm, and the acupuncture density is 5-10 needles / cm²; The acupuncture needles are of double or triple hook structure and are size 28-36.

2. The method for preparing a long-filament geotextile with added tourmaline powder as described in claim 1, characterized in that, The preparation of the composite masterbatch includes the following steps: Surface-modified tourmaline powder is mixed with alloyed polymer matrix at a mass ratio of 20:80-40:60, and dispersant and lubricant are added. Melt blending is carried out using a two-stage twin-screw extruder, with a first-stage extrusion temperature of 220-240℃, a second-stage extrusion temperature of 240-260℃, and a screw speed of 300-400 rpm. After water cooling and pelletizing, the extrudate is used to obtain a composite masterbatch with uniform tourmaline content.

3. The method for preparing a long-filament geotextile with added tourmaline powder as described in claim 1, characterized in that, The gradient spinning process includes the following steps: The composite masterbatch is conveyed to the spinning box via a screw extruder. The spinning box is divided into three temperature zones: The temperature in the feeding zone is 260-270℃; The temperature in the metering zone is 255-265℃; The temperature in the spinneret area is 250-260℃; The spinneret has irregularly shaped holes with an orifice diameter of 0.15-0.25 mm.

4. The method for preparing a long-filament geotextile with added tourmaline powder as described in claim 1, characterized in that, The synergistic nanofiber web formation includes the following steps: Core-shell nanofibers were prepared using coaxial electrospinning technology, with polylactic acid as the core and polyurethane loaded with nano-titanium dioxide as the shell. The electrospinning parameters were set as follows: voltage 18-25kV, receiving distance 12-18cm, and feed rate 0.5-1.5mL / h. During the filament web laying process, nanofibers are simultaneously and evenly sprayed onto the filament web, with the mass of nanofibers accounting for 1-5% of the mass of the filament web.

5. The method for preparing a long-filament geotextile with added tourmaline powder as described in claim 1, characterized in that, The post-activation processing of the function includes the following steps: The needle-punched and consolidated geotextile was subjected to low-temperature plasma treatment. The gas medium was a mixture of argon and oxygen with a volume ratio of 3:1-5:

1. The processing parameters are: power density 50-100W / m², processing time 10-30s, and working air pressure 20-50Pa. After treatment, the geotextile is subjected to heat setting at a temperature of 120-140℃ for 30-60 seconds.

Citation Information

Patent Citations

  • Manufacturing technology of 3-micron filtering material

    CN108677379A

  • Manufacturing equipment for functional ultra-high molecular weight polyethylene fibers

    CN214361879U